1983
DOI: 10.2337/diacare.6.2.140
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Hand Abnormalities to Diabetes and Diabetic Retinopathy

Abstract: The hands of 299 diabetic patients with and 161 without retinopathy were examined for abnormalities. Almost all abnormalities were finger joint contractures resulting in limited joint mobility (LJM) and/or Dupuytren's contractures (DC). Both LJM and DC occurred not only in insulin-dependent diabetes (IDDM) but also in non-insulin-dependent diabetes (NIDDM). In retinopathy patients LJM and DC occurred in 48% and 36% of patients, respectively, compared with 24% and 16% in those without retinopathy. These differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
42
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 0 publications
5
42
0
Order By: Relevance
“…Limitation of motion may also occur secondary to microangiopathy or neuropathy (13). The reported prevalence of limited joint mobility ranges from 11% to 55% in patients with insulin-dependent diabetes mellitus (IDDM) (3-5, [14][15][16][17][18][19][20][21][22][23][24], from 30% to 70% in patients with non-insulindependent diabetes mellitus (18,21,23-25), and from 1% to 20% in nondiabetic subjects (3,17,19,21,23,24). These wide ranges in reported prevalence are due to differences among the studies in terms of population selection, assessment methodology, and definition of limited joint mobility.…”
mentioning
confidence: 99%
“…Limitation of motion may also occur secondary to microangiopathy or neuropathy (13). The reported prevalence of limited joint mobility ranges from 11% to 55% in patients with insulin-dependent diabetes mellitus (IDDM) (3-5, [14][15][16][17][18][19][20][21][22][23][24], from 30% to 70% in patients with non-insulindependent diabetes mellitus (18,21,23-25), and from 1% to 20% in nondiabetic subjects (3,17,19,21,23,24). These wide ranges in reported prevalence are due to differences among the studies in terms of population selection, assessment methodology, and definition of limited joint mobility.…”
mentioning
confidence: 99%
“…Rosenbloom concedes that there is a lack of relationship between collagen glycosylation and LJM, and presumably to thick skin. The statistical relationship described by Monnier [7] showed a correlation coefficient (r) between joint stiffness and skin collagen fluorescence of 0.34. This may have struggled to significant levels, but the measure of dependance of one variable on the other (r2), of 0.12, indicates that we must look elsewhere for causative association.…”
Section: The Skin In Diabetes Mellitusmentioning
confidence: 99%
“…The stable end-products of the non-enzymatic browning reaction which are thought to be responsible for increased cross-linking, packing, and stiffening of collagen are fluorescent. Monnier et al [6] demonstrated that fluorescence of skin collagen increased linearly with age, but that 95% of 41 Type 1 (insulin-dependent) diabetes patients had abnormal increases for age, and that the degree of skin collagen fluorescence correlated with the presence of retinopathy, nephropathy, and LJM.The suggestion that cautious interpretation of LJM is needed because of its frequency in the normal population is in reference to a study [7] in older patients, in whom age and occupation-related changes in the finger joints confound interpretation, as does the presence of Dupuytren contracture. This is most definitely not the case in the young patients originally and subsequently reported by numerous investigators.…”
mentioning
confidence: 99%
See 2 more Smart Citations